Attention to students in hospitals (Journal of Parents and Teachers, 2014)
Nowadays, it is intended that children who are hospitalized receive a pedagogical attention that allows them to continue learning and continue to develop in full as normal as possible. This article explains the mission of Hospital Pedagogy and the way in which they carry it out.
Keywords: hospital pedagogy; children in hospitals; teaching; hospital classrooms.